Savings after retirement - Eric French; John Bailey Jones; Rory McGee (Institute for Fiscal Studies (IFS), 2022)
Retired households, especially those with high lifetime income, decumulate their wealth very slowly, and many die leaving large estates. The three leading explanations for the 'retirement savings puzzle' are the desire to insure against uncertain lifespans and medical expenses, the desire to leave bequests to one's heirs, and the desire to remain in one's own home. We discuss the empirical strategies used to differentiate these motivations, most of which go beyond wealth to exploit additional features of the data. The literature suggests that all the motivations are present, but has yet to reach a consensus about their relative importance.
Keywords: 330; Retirees; saving; precautionary saving; health care costs; inheritance; insurance coverage; USA; Rentner; Sparen; Vorsichtssparen; Gesundheitskosten; Erbe; Versicherungsschutz; USA